Seed dormancy and control of germination in Sisymbrella dentata (L.) O.E. Schulz (Brassicaceae). (1st July 2018) - Puglia, G.; Carta, A.; Bizzoca, R.; Toorop, P.; Spampinato, G.; Raccuia, S. A.
Abstract: Seed germination responsiveness to environmental cues is crucial for plant species living in changeable habitats and can vary among populations within the same species as a result of adaptation or modulation to local climates. Here, we investigate the germination response to environmental cues of Sisymbrella dentata (L.) O.E. Schulz, an annual endemic to Sicily living in Mediterranean Temporary Ponds (MTP), a vulnerable ecosystem. Germination of the only two known populations, Gurrida and Pantano, was assessed over a broad range of conditions to understand the role of temperatures, nitrate, hormones (abscisic acid – ABA and gibberellins – GA) and after‐ripening in dormancy release in this species. Seed germination responsiveness varied between the two populations, with seeds from Gurrida germinating under a narrower range of conditions. Overall, this process in S. dentata consisted of testa and endosperm rupture as two sequential events, influenced by ABA and GA biosynthesis. Nitrate addition caused an earlier testa rupture, after‐ripening broadened the thermal conditions that allow germination, and alternating temperatures significantly promoted germination of non‐after‐ripened seeds. Primary dormancy in S. dentata seeds likely allows this plant to form a persistent seed bank that is responsive to specific environmental cues characteristic of MTP habitats.